Human beta-defensin 3 is up-regulated in cutaneous leprosy type 1 reactions. - Anna L Cogen; Stephen L Walker; Chrissy H Roberts; Deanna A Hagge; Kapil D Neupane; Saraswoti Khadge; Diana N J Lockwood (PLoS Neglected Tropical Diseases)
Background Leprosy, a chronic granulomatous disease affecting the skin and nerves, is caused by Mycobacterium leprae (M. leprae). The type of leprosy developed depends upon the host immune response. Type 1 reactions (T1Rs), that complicate borderline and lepromatous leprosy, are due to an increase in cell-mediated immunity and manifest as nerve damage and skin inflammation. Owing to the increase in inflammation in the skin of patients with T1Rs, we sought to investigate the activation of the innate immune system during reactionary events. Specifically, we investigated the expression levels of human beta-defensins (hBDs) 2 and 3 in the skin of patients with T1Rs, in keratinocytes, and in macrophages stimulated with M. leprae and corticosteroids. Results Skin biopsies from twenty-three patients with Type 1 reactions were found to have higher transcript levels of hBD3 as compared to fifteen leprosy patients without Type 1 reactions, as measured by qPCR. Moreover, we observed that keratinocytes but not macrophages up-regulated hBD2 and hBD3 in response to M. leprae stimulation in vitro. Corticosteroid treatment of patients with T1Rs caused a suppression of hBD2 and hBD3 in skin biopsies, as measured by qPCR. In vitro, corticosteroids suppressed M. leprae-dependent induction of hBD2 and hBD3 in keratinocytes. Conclusions This study demonstrates that hBD3 is induced in leprosy Type 1 Reactions and suppressed by corticosteroids. Furthermore, our findings demonstrate that keratinocytes are responsive to M. leprae and lend support for additional studies on keratinocyte innate immunity in leprosy and T1Rs. Trial registration Controlled-Trials.com ISRCTN31894035.